Impact of twin typhoons on the upper ocean environment across the Northwest Pacific ocean - M.V. Subrahmanyam (Tropical Cyclone Research and Review)
Two typhoons, Saola and Damrey, moved across the Northwest Pacific Ocean (NPO) between July 27, 2012, and August 4, 2012. During this period, the oceanographic response was studied. The study examined variations in Sea Surface Temperature (SST) and Mix Layer Depth (MLD) in response to twin typhoons using satellite data from QuickSCAT wind, reanalysis data from OISST, and Argo data. On August 1, 2012, typhoon Damrey's right side experienced the greatest SST dip of 3.6 °C because of mixing. Typhoon Damrey had an influence on typhoon Saola, which caused a weaker SST cooling of 2.5 °C. During the passage of the twin typhoons, the area around typhoon Saola observed the most noticeable change in MLD, which went from 15 m to 85 m. The Ekman pumping effect led to modifications in the subsurface layer, which improved SST cooling and caused MLD deepening.